Multimedia-Assisted Learning among Lebanese Teachers - Jabbour, Khayrazad Kari (Journal of Education and Vocational Research, 2013)
Multimedia learning consists of graphics and texts. Learning occurs when the learners create mental representations from combining the text and relevant graphics in the lessons. Incorporation of multimedia learning in teaching can lead education to a higher level than traditional teaching techniques. The aim of this study is to investigate the extent to which multimedia is incorporated in classroom teaching among Lebanese educators. A small scale survey from 50 middle school teachers of 10 different schools selected from various areas in Lebanon was undertaken. The survey results were compared and tested in order to evaluate whether or not the teachers integrate multimedia in classroom teaching. If they do, this study aims to identify the multimedia elements they frequently use. However, if not, this study aims to find out the causes for not adopting multimedia in their classroom teaching.